Antibacterial Thiopeptide GE2270-Congeners from Nonomuraea jiangxiensis - Kuan-Chieh Ching; Elaine J. Chin; Mario Wibowo; Zann Y. Tan; Lay-Kien Yang; Deborah C. Seow; Chung-Yan Leong; Veronica W. Ng; Siew-Bee Ng; Yoganathan Kanagasundaram (Molecules, 2022)
Thiopeptides are macrocyclic natural products with potent bioactivity. Nine new natural thiopeptides (1–9) were obtained from a Nonomuraea jiangxiensis isolated from a terrestrial soil sample collected in Singapore. Even though some of these compounds were previously synthesized or isolated from engineered strains, herein we report the unprecedented isolation of these thiopeptides from a native Nonomuraea jiangxiensis. A comparison with the literature and a detailed analysis of the NMR and HRMS of compounds 1–9 was conducted to assign their chemical structures. The structures of all new compounds were highly related to the thiopeptide antibiotics GE2270, with variations in the substituents on the thiazole and amino acid moieties. Thiopeptides 1–9 exhibited a potent antimicrobial activity against the Gram-positive bacteria, Staphylococcus aureus with MIC90 values ranging from 2 µM to 11 µM. In addition, all compounds were investigated for their cytotoxicity against the human cancer cell line A549, none of the compounds were cytotoxic.